2014
DOI: 10.1089/lap.2013.0578
|View full text |Cite
|
Sign up to set email alerts
|

Laparoendoscopic Single-Site Ureteroureterostomy with Intraoperative Retrograde Ureteroscopy-Assisted Technique for Benign Proximal and Middle Ureteral Strictures: A Single-Center Experience

Abstract: LESS-UU is feasible and safe for repairing benign proximal and middle ureteral stricture. The intraoperative retrograde ureteroscopy-assisted technique during LESS-UU is useful for localizing the stricture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Laparoscopic UU has been reported for the treatment of benign ureteral strictures, iatrogenic injury during gynecological surgery, and retrocaval ureter [1] , [4] . UU is traditionally performed through open surgery, but it has recently been increasingly performed through several minimally invasive techniques, including laparoscopic, robot-assisted, and LESS UU [1] , [2] , [3] . The portion of the affected ureter must be completely removed surgically, although only a minimum length should be excised.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Laparoscopic UU has been reported for the treatment of benign ureteral strictures, iatrogenic injury during gynecological surgery, and retrocaval ureter [1] , [4] . UU is traditionally performed through open surgery, but it has recently been increasingly performed through several minimally invasive techniques, including laparoscopic, robot-assisted, and LESS UU [1] , [2] , [3] . The portion of the affected ureter must be completely removed surgically, although only a minimum length should be excised.…”
Section: Discussionmentioning
confidence: 99%
“…Chow et al reported an observation method using a rigid ureteroscope during laparoscopic surgery to identify a stricture [6] . Tang et al reported the use of rigid ureteroscope during LESS UU and described the availability of this instrument in developing countries; thus, this technique may have widespread applicability [3] . However, it is necessary to place the patient in the lithotomy position when using a rigid scope and if the laparoscopic procedure is combined with the lateral decubitus position, the acrobatic posture must be employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After endotracheal intubation following general anesthesia, patients were then passively placed in a position, which is a hyper extensive lithotomy position with the body in a 45 recumbent position on the surgical side up. The abdomen and perineum were disinfected together, and an arcuate incision of ∼2 cm was made at the umbilicus (Figure 1, point A), followed by the insertion of a Veress needle and inflation of the umbilicus with carbon dioxide to maintain the intra-abdominal pressure at 12-14 mmHg, as described by Tang et al (12). A 12 mm trocar for the laparoscope was then placed through the incision.…”
Section: Operative Techniquementioning
confidence: 99%
“…Several authors have recommended the use of a rigid ureteroscope to confirm the length of the stricture. 56, 57 Recently, a single surgeon operative experience with robotic UU for upper, mid and distal ureteral strictures found that patients had 100% recurrence-free survival at 3 years follow-up; however, this procedure is technically limited by complex port placement. 58…”
Section: Laparoscopic/robotic Approaches To Ureteral Reconstructionmentioning
confidence: 99%